Genotype and clinical phenotype characteristics of MAX germline mutation–associated pheochromocytoma/paraganglioma syndrome - Lian, Bijun; Lu, Jun; Fang, Xudong; Zhang, Yiming; Wang, Wei; He, Yi; Yu, Hongyuan; Li, Feiping; Wang, Junwei; Chen, Weiying; Qi, Xiaoping (Frontiers in Endocrinology, 2024)
Objective: The aim of this study was to investigate the genotypic and clinical phenotypic characteristics of MAX germline mutation–associated pheochromocytoma (PCC) and paraganglioma (PGL). Methods: We retrospectively analyzed the family investigation data and clinical genetic characteristics of six individuals from three independent families with PCC carrying MAX germline mutations from December 2005 to March 2024. A literature review was then conducted of the six carriers and another 103 carriers from the other 84 families with MAX germline mutations reported previously. Results: There were 109 patients in 87 families with all five exons and 53 types of MAX germline mutations. p.R33* (c.97C>T; 21.1%), p.R75* (c.223C>T; 13.8%), and p.A67D (c.200C>A; 7.3%), which accounted for 42.2% of mutations detected, were the most common mutations. Moreover, 101 (92.7%) patients developed PCCs, including 59 bilateral PCCs and 42 unilateral PCCs, and 19 (18.8%) patients showed metastasis. The mean age at diagnosis was 32.8 ± 12.6 (13-80) years. The male-to-female ratio was 1.3:1. In 11 (10.9%) patients, the PCC was accompanied by chest or abdominal PGL, and one other patient had sole head and neck PGL. Nine (8.3%) patients also had functional pituitary adenomas, 11 (10.9%) developed other neuroendocrine tumors (NETs), and 7 (6.4%) presented with concomitant non-NET. Meanwhile, MAX-p.Q82Tfs*89 and p.E158A mutations are reported for the first time in this study. Conclusion: MAX germline mutations may cause new types of multiple endocrine neoplasia. A comprehensive baseline assessment of neural crest cell–derived diseases is recommended for all individuals with MAX germline mutations. The risk of bilateral and metastatic PCCs should also be considered.